RATIONAL DOSAGE REGIMEN OF ANTIBIOTICS - Faqir Hussain Khan (Journal of University Medical & Dental College, 2020)
Antibiotics play an important role in the treatment of various infectious diseases in man and domestic animals. For treating microbial infections effectively, it is essential that an effective concentration of antibacterial drug be rapidly attained at the focus of infection and that it be maintained for an adequate time. The concentration achieved varies with systemic availability of the drug based on its dosage form, dosing rate, routs of administration and ability to gain access to the infection site. The concentration also varies with the physicochemical characteristics of the drug which subsequently influence the extent of absorption, pattern of distribution and elimination mechanisms (pharmacokinetics characteristics).